PENGARUH JENIS KEMASAN TERHADAP KUALITAS BUAH JERUK SIAM (Citrus nobilis var. microcarpa) PADA PERIODE MASA SIMPAN: The effect of type of packaging on the quality of fruit of siam orange (Citrus nobilis var. microcarpa) in the storage period - Ari Rizki (PAKIS JOURNAL INSTITUTE, 2023)
Siamese orange is one of the fruits that produce vitamin C, containing 20-60 mg/100 ml. Siamese citrus production in Sambas Regency in 2016 – 2017 experienced an increase in growth of 28,937 quintals. In 2017 – 2018 it was 249,863 quintals. So that the total increase in Siamese oranges in 2016 – 2018 was 220,899 quintals. The purpose of this study was to analyze the effect of the type of packaging on the quality of Siamese oranges during the shelf-life period. The approach technique used in this study is true experimental, with analysis using the ANOVA test. Based on the results of the analysis using the iodimetric method, it was found that for the treatment at room temperature of 27 C with a weight of 330 g there was an increase in the content of vitamin C by 6.96%, while for the skin it decreased by 14.25%. For a sample weight of 340 g, vitamin C levels increased by 1.34% and for skin, vitamin C levels decreased by 25.37%. Based on the analysis of the ANOVA test, it was found that at room temperature treatment of 27 C Fcount (1.05) was smaller than Ftable 5% (5.99) and for 1% (13.75), this showed no significant difference. Meanwhile, for the freezer temperature sample - 10 C, Fcount (1.25) is smaller than Ftable (5.99), while for 1% (13.75), the data is said to be not significantly different.